Uptake of Mercury Ion in a Wetland Plant, Canna Sp. - . Suhendrayatna; Henny Marlina; Muhammad Zaki; . Elvitriana (Syiah Kuala University, 2015)
Canna Sp. is one of the plants that can live in conditions of wetland cultivated in freshwater courses, which often serve as recipients for domestic and other sorts of wastewater. In the context of its life ability, this study deals to investigate the capacity of Canna Sp. in uptake toxic heavy metal mercury from a wetland system. Canna Sp. was cultivated in a polybag contained wastewater for a couple months to reach acclimatization. The wastewater contained mercury ions in different concentrations of 1.2; 0.96 and 0.36 mg-Hg/L. Each polybags contained five stems of Canna Sp. Control media (contain no mercury in media) were also prepared for these treatments. During 14 days of the experiment, the atmospheric air and water temperature (30+3 oC is optimum) were maintained and every five days, length of stems, concentration of mercury ion in water phase, and its tissue were analyzed. The concentration of mercury in shoots, leaves, and roots were analyzed by Atomic Absorption Spectrophotometer, Shimadzu AA 6300 after destructed using TCLP method. Results showed that Canna Sp. has resistant a survival on water phase containing mercury and it inhibits the growth of Canna Sp. in the log phase. The highest mercury ion uptake by Canna Sp. occurred in the root (1.16 – 1.34 mg-Hg/kg) compared to the leaves (0.05 – 0.33 mg-Hg/kg) and the shoots (0.29-0.69 mg-Hg/kg). These results reached to the conclusion that Canna Sp. has a potential for mercury phytoremediation application in a wetland system.